1992
DOI: 10.2307/3315609
|View full text |Cite
|
Sign up to set email alerts
|

Goodness of fit for the inverse Gaussian distribution

Abstract: For testing the fit of the inverse Gaussian distribution with unknown parameters, the empirical distribution‐function statistic A2 is studied. Two procedures are followed in constructing the test statistic; they yield the same asymptotic distribution. In the first procedure the parameters in the distribution function are directly estimated, and in the second the distribution function is estimated by its Rao‐Blackwell distribution estimator. A table is given for the asymptotic critical points of A2. These are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Folks and Chhikara [24] found that the fit of the IG2 to this data is not satisfactory. The same conclusion may be drawn from O'Reilly and Rueda [11] who found a p-value of 0.04 by using a Monte Carlo approximation of the distribution of the AD test statistic with the parameters replaced by their ml estimates. The modified AD test of Pavur et al [9] barely accepts the IG2 model (test statistic = 8.273, 95% interpolated critical value = 8.2885, p-value=slightly over 5%).…”
Section: Examplesupporting
confidence: 67%
See 3 more Smart Citations
“…Folks and Chhikara [24] found that the fit of the IG2 to this data is not satisfactory. The same conclusion may be drawn from O'Reilly and Rueda [11] who found a p-value of 0.04 by using a Monte Carlo approximation of the distribution of the AD test statistic with the parameters replaced by their ml estimates. The modified AD test of Pavur et al [9] barely accepts the IG2 model (test statistic = 8.273, 95% interpolated critical value = 8.2885, p-value=slightly over 5%).…”
Section: Examplesupporting
confidence: 67%
“…We also find non-significant results at the 5% level with the modified KS (test statistic = 0.176) and AD tests (test statistic = 6.552, p-value between 10% and 20%) of Edgeman et al [8] and Pavur et al [9] and with the T 2 test (p − value = 0.372) of Natarajan and Mudholkar [16]. On the contrary, O'Reilly and Rueda [11] rejected the IG2 hypothesis at the 5% level based on the asymptotic distribution of the AD test statistic (p-value < 0.025) and Gunes et al [10] concluded similarly with their modified WA test. Also, the IG2 can be rejected at the 5% level by the independence Z-test of Mudholkar et al [14] (p-value = 0.037) and by the entropy test of Mudholkar and Tian [15] (K mn = 2.675 found for m = 3, p-value ∼ = 0.05).…”
Section: Examplementioning
confidence: 56%
See 2 more Smart Citations
“…In their study, at some alternative distributions, and with reasonable, not large, sample sizes, the exact EDF goodness-of-fit tests based on this transformation behave pretty well comparing with the other approximate EDF goodness-of-fit tests. The other goodness-of-fit tests for inverse Gaussian distributions using EDF statistics were given by Edgeman et al [3], O'Reilly and Rueda [6], and Pavur et al [7]. For detailed references, see Seshadri [10].…”
Section: Be a Random Sample Of N Nonnegative Random Variables From A mentioning
confidence: 99%